Shelf Life of Chicken Samosa Incorporated with Custard Apple (Annona Squamosa) Peel Powder : doi: 10.5958/2581-6616.2021.00006.2 - Lonarkar, A. G.; Rathod, K. S.; Ambadkar, R. K.; Patil, P. S.; Dhagare, L. G. (Journal of Meat Science, 2022)
Very few studies have been documented regarding the use of natural antioxidants like Custard Apple Peel Powder (CPeP)  in meat products over synthetic antioxidants (BHT). Therefore, the current study was aimed to evaluate the effect of  CPeP on the shelf life of chicken Samosa. The smashed boiled potato (10%) was mixed with minced (6 mm) breast  fillets along with an onion (20%), condiments, spices mix, and salt which were then cooked on the preheated pan with  continuous stirring till the appearance of golden brown colour and used as filler material for samosa. Antioxidants of  1% CPeP and BHT@125 mg/kg were added separately as treatments. About 20g of samosa mixture was filled into each  dough sheet in a triangular shape and stored under refrigeration (4±1°C) temperature. During the storage period of 12  days the pH, tyrosine, and peroxide value increased significantly (P
Keywords: Chicken Samosa; Custard apple peel powder; Quality analysis; Shelf life; Synthetic antioxidant